Reinforcing entrepreneurs’ economic rights in the age of digital constitutionalism: legal institutions and judicial challenges - Nafisa Aslonova (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The protection of entrepreneurs’ economic rights is evolving rapidly amid global digital transformation. This article analyzes how constitutional and judicial systems adapt to emerging digital realities, using the case of Uzbekistan as a focal point. It examines how foundational constitutional guarantees, legislative initiatives, and judicial practices shape an environment conducive to entrepreneurial freedom. Special attention is given to challenges in digital justice, such as the handling of digital evidence, cross-border disputes, and cyber risks. The article concludes with strategic recommendations for integrating constitutional safeguards with modern legal tools to protect entrepreneurs in the digital economy.